Afghanistan : Building an Effective State, Priorities for Public Administration Reform - World Bank (World Bank, Washington, DC, 2012)
This report looks at the implications for public administration reform over the next 5-10 years, and proposes a priority agenda for action by the Government of Afghanistan (GOA) and the donor community. The report reviews the prospects and priorities for public administration reform in three key areas: building an effective civil service, improving local governance and service delivery, and making government accountable to the people. This report has made the case that public administration reform in Afghanistan is both very important and very difficult: very important because it will provide the Government o f Afghanistan with the capacity to respond to popular demands for good governance and improved service delivery; very difficult, because of the inherent challenges o f institutional change, especially in the current political and security situation in Afghanistan. Public Administration Reform (PAR) is a long-term task -This will require persistent effort over time, as well as innovative approaches to improve service delivery in the short and medium terms. Afghanistan's experience over the past five years, as well as lessons from other fragile states, provide some clues about how to go about public administration reform.